The impact of residual mitral regurgitation on outcomes in patients with primary mitral regurgitation undergoing mitral valve transcatheter edge-to-edge repair. (3rd October 2022) - Waldschmidt, L; Koell, B; Ludwig, S; Weimann, J; Schirmer, J; Reichenspurner, H; Blankenberg, S; Conradi, L; Schofer, N; Kalbacher, D
Abstract: Background: Mitral valve transcatheter edge-to-edge repair (M-TEER) has become an established therapeutic approach for patients at high surgical risk with relevant mitral regurgitation (MR). While robust data exists on the impact on outcome of residual MR (rMR) following M-TEER for patients with secondary MR, data on the exact role of rMR in primary MR is currently scarce. This study aimed to investigate the adverse impact of relevant rMR on outcomes in a real-world population of patients undergoing M-TEER for primary MR. Methods: This single-center, retrospective analysis includes data from 364 consecutive patients with relevant primary MR treated by M-TEER at a high-volume center between 11/2008–01/2020. Post-procedural rMR was defined as the MR grade determined by transthoracic echocardiography before discharge. Primary endpoint was defined as all-cause mortality; the composite secondary endpoint included all-cause mortality or rehospitalization for heart failure at 1-year follow-up. Kaplan-Meier estimates and Cox regression analysis were performed to study the impact of rMR on outcomes. Results: In this high-risk population (mean age 78.6±7.4 years, 55.2% male, median logistic EuroSCORE 17.5% [interquartile range 10.4; 27.7], median STS Score 4.4% [interquartile range 2.8; 6.6]), rMR at discharge was successfully reduced to none/mild (≤1+) in 191 (52.5%) patients. Moderate rMR (=2+) was found in 129 (35.4%) patients and moderate-to-severe or severe rMR (≥3+) was present in 44 (12.1%) patients post-procedurally. Patients with rMR≥3+ presented with enlarged left atria at baseline (left atrium volume: rMR≤1+: 101.8ml [interquartile range (IQR): 77.3, 129.6]; rMR=2+: 113.7ml [IQR: 90.4, 154.3]; rMR≥3+: 123.0ml [IQR: 92.9, 147.5]; p=0.009) and dilated left ventricle (left ventricle end-diastolic diameter: rMR≤1+: 54.8±8.7mm; rMR=2+: 59.7±9.8mm; rMR≥3+: 59.1±10.0mm; p<0.001). Baseline NT-proBNP was significantly higher in patients with relevant post-precedural rMR (≥3+) compared to patients with none/mild or moderate rMR (p=0.038). Kaplan-Meier analyses demonstrate significant differences for the primary and secondary endpoints (Figure 1). Compared to patients with none/mild and moderate rMR, higher rates of all-cause mortality were reported in patients with rMR≥3+ at 1-year follow-up (rMR≤1+: 16.2%; rMR=2+: 23.9%; rMR≥3+: 40.0%; p[log-rank] = 0.007). Moreover, adjusted cox regression analysis identified rMR≥3+ as an independent predictor of adverse outcome (Hazard Ratio = 2.70 [95%-confidence interval: 1.12–6.50]; p=0.027). Conclusions: Our data provides first evidence that clinical outcome in patients with primary MR undergoing M-TEER is impacted by the grade of post-procedural rMR. This analysis, therefore, emphasizes the importance of minimizing rMR to the lowest possible grade in order to achieve optimal long-term survival. Funding Acknowledgement: Type of funding sources: None.